PENGEMBANGAN UMKM MELALUI PLATFORM E-COMMERCE BERBASIS AI UNTUK MENINGKATKAN PENJUALAN PRODUK LOKAL - Rahsel, Yoeyong; Waziana, Winia; Saputra, Ricco Herdiyan; Pratomo, Panji Andhika (Jurnal AbdiMas Nusa Mandiri, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is a top priority in efforts to strengthen the national economy. The UMKM Natar Community serves as a platform for MSME actors in Natar District, South Lampung Regency, consisting of 113 members engaged in sectors such as culinary, crafts, fashion, agriculture, and health. Despite its great potential, this community still faces several challenges, including the suboptimal use of digital media for marketing, conventional business management practices, and limited human resource skills. To address these issues, digital transformation is believed to be an effective solution to support MSME growth. This community service activity aims to provide outreach, training, and mentoring to UMKM Natar members regarding digital transformation and skills enhancement in product marketing management. Through methods involving education, technology application, and training in digital marketing, business management, and human resource development, this activity successfully improved participants' understanding and ability to use technology, including Artificial Intelligence (AI), to support the online management and marketing of their businesses.